Electrodeposited MnCO3 as a High Performance Electrode Material for Supercapacitor. Issue 24 (25th June 2018) - Vardhan, P. Vishnu; Idris, Mustapha Balarabe; Ramanathan, V.; Devaraj, S.
Abstract: MnCO3 as an electrode material for supercapacitor is slowly gaining momentum. So far, wet chemical methods have been used to synthesize MnCO3 for supercapacitor applications. The electrode fabrication of thus prepared MnCO3 requires a certain percentage of conductive additive and binder; both of them do not contribute significantly to the measured capacitance. Herein, we report electrodeposition of MnCO3 and its capacitance properties. MnCO3 has been electrodeposited from an aqueous mixture of MnSO4 and Na3 C6 H5 O7 by chronopotentiometry. X‐ray diffraction and Raman spectroscopic studies confirm the formation of MnCO3 . Microscopic studies reveal the formation of micron‐sized spherical particles by the agglomeration of sub‐micron sized cubes. Electrodeposited MnCO3 delivers a specific capacitance of 194 F g −1 at a specific current of 0.5 A g −1 and demonstrates good rate capability. Further, it also exhibits high cycling stability over 10, 000 cycles with retention of 92% of its initial specific capacitance value and 100% coulombic efficiency. Abstract : Electrodeposited MnCO3 not only enables its use as an electrode without conductive additive and binder but also delivers high specific capacitance, good rate capability and stable cycle‐life with excellent coulombic efficiency.